Laboratory animal science and experimentation in India : Review of the last decade (Journal of Laboratory Animal Science, 2018)
Ever since the revival of the Prevention of Cruelty to Animals  Act (1960 )in 1998, the law was amended and implemented  with renewed vigor, the animal welfare and laboratory animal  experimentation has seen a major change. The strict imple mentation of the law during the early part of the decade led  to the spilling of skeletons from cupboards of some very well  known and established institutions in India. The implemen tation of the law not only revealed the lack of basic facilities  and poor and unhygienic conditions in animal facilities, it also  revealed the laid back attitude of those who were responsible.  The increase in awareness that was achieved through the  animal welfare movement in India was enormous. It has  led to the improvement of laboratory animal facilities in  several institutions and the commissioning and constitution  of Institutional Animal Ethics Committees (IAEC) in all  the CPCSEA (Committee for the Purpose of Control and  Supervision of Experiments on Animals), Animal Welfare  Division, Ministry of Environment and Forests, Government  of India, registered organizations. The IAEC is in turn playing  a major role in improving the welfare of the animals used  for experiments. Nevertheless, the improvement of animal  facilities in the Pharmaceutical industry and the Contract  Research Organizations (CRO) to this day are driven more  by the need to attract and capture business than a true change  in the heart for the welfare of animals. The race for acquiring  Good Laboratory Practices and Association for Assessment  and Accreditation of Laboratory Animal Care International  (AAALAC International) accreditation in the private industry,  and the contrasting laid back attitude in the Government sector  as was evident before 1998 is a clear indication of this fact.  It may also be considered here that the threat of the law and  negative public opinion has played a significant effect on the  Government Institutions and several of them did release funds  and have improved the animal facilities in their respective  organizations.
Keywords: laboratory animals; experimentation; india